Aberrant promoter hypermethylation of selected apoptotic genes in childhood acute lymphoblastic leukemia among north indian population - Nikbakht, M.; Jha, A.K.; Malekzadeh, K.; Askari, M.; Mohammadi, S.; Marwaha, R.K.; Kaul, D.; Kaur, J. (Experimental Oncology, 2017)
Promoter hypermethylation mediates gene silencing in many neoplasms. Acute leukemia has been reported to harbor multiple genes aberrantly silenced by hypermethylation. Aim: In present study, we investigated the prevalence of hypermethylation of caspase-8 (CASP8), TMS1 and DAPK genes in correlation with clinicopathological factors in childhood acute lymphoblastic leukemia (ALL). Materials and Methods: A case-control study has been conducted based on bone marrow and peripheral blood samples from 125 ALL patients and 100 sex-age matched healthy controls. Methylation specific polymerase chain reaction (PCR) and bisulfite sequencing PCR was performed to analyze the methylation status of these genes. Reverse transcription PCR and real time PCR was carried out to determine changes in the mRNA expression level of the genes due to hypermethylation. Results: Hypermethylation of the 5´CpG islands of the CASP8, TMS1 and DAPK gene promoters was found in 3.2, 6.4, and 13.6% of 125 childhood ALL samples from north Indian population, respectively. There were significant differences in pattern of hypermethylation of TMS1 (p = 0.045) and DAPK (p < 0.001) between patients and healthy controls. Down-regulation of mRNA expression was found in cases in which CASP8, TMS1 and DAPK were hypermethylated. Conclusions: The present study indicated the impact of hypermethylation-mediated inactivation of CASP8, TMS1 and DAPK genes, which is associated with risk of childhood ALL. This abnormality occurs in leukemogenesis and it may be used as a biomarker and for predicting the prognosis of ALL.